2019
DOI: 10.3390/antibiotics8030110
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Toxicity of Azithromycin Results in Aerobic Glycolysis and DNA Damage of Human Mammary Epithelia and Fibroblasts

Abstract: Mitochondria evolved from free-living bacteria via endocytosis within eukaryotic host cells millions of year ago. We hypothesized that antibiotics cause mammalian mitochondrial damage while causing bacterial lethality. Mitochondrial toxicity of azithromycin in human mammary epithelia MCF-12A and fibroblasts were tested by fluorescent and transmission electron microscopy. Gene expression and DNA damage were tested by real-time polymerase chain reaction (qPCR) and ELISA. We found azithromycin suppressed the mito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…That step is eliminating antibiotics in the cell culture media that donor cells are incubated in before isolating mitochondria for transplantation. We have shown that antibiotics cause tremendous damage to mitochondria inducing severe mitochondrial dysfunction [20] [21] [22]. This is because mitochondria are evolutionary bacteria and share similar ribosomes and protein synthesis machinery as their ancient relative.…”
Section: Discussion Conclusion and Future Directionmentioning
confidence: 99%
“…That step is eliminating antibiotics in the cell culture media that donor cells are incubated in before isolating mitochondria for transplantation. We have shown that antibiotics cause tremendous damage to mitochondria inducing severe mitochondrial dysfunction [20] [21] [22]. This is because mitochondria are evolutionary bacteria and share similar ribosomes and protein synthesis machinery as their ancient relative.…”
Section: Discussion Conclusion and Future Directionmentioning
confidence: 99%
“…Align with this finding, tetracyclines like doxycycline and minocycline have been shown to impair mitochondrial biogenesis ( Kroon and Van den Bogert, 1983 ), mitochondrial respiratory chain activity ( Chatzispyrou et al, 2015 ), and mitochondrial protein synthesis ( Fuentes-Retamal et al, 2020 ). Moreover, the macrolide antibiotic azithromycin has been shown to cause disruption of the Ψ mito ( Xiao et al, 2019 ), ROS production ( Jiang et al, 2019 ), and cytochrome c release ( Salimi et al, 2016 ).…”
Section: Reactive Oxygen Species Modulation By Approved Drugsmentioning
confidence: 99%
“…Inhibit cancer proliferation [40,134] Mitigates muscle fatigue [238] AMPK activation [238] Mitochondrial membrane potential disruption [36] ROS production [260] Cytochrome c release [261] 500 250…”
Section: Azithromycin Macrolidementioning
confidence: 99%